Altering the speed of a DNA packaging motor from bacteriophage T4. Issue 19 (13th September 2017) - Lin, Siying; Alam, Tanfis I.; Kottadiel, Vishal I.; VanGessel, Carl J.; Tang, Wei-Chun; Chemla, Yann R.; Rao, Venigalla B.
Abstract: The speed at which a molecular motor operates is critically important for the survival of a virus or an organism but very little is known about the underlying mechanisms. Tailed bacteriophage T4 employs one of the fastest and most powerful packaging motors, a pentamer of gp17 that translocates DNA at a rate of up to ∼2000-bp/s. We hypothesize, guided by structural and genetic analyses, that a unique hydrophobic environment in the catalytic space of gp17-adenosine triphosphatase (ATPase) determines the rate at which the 'lytic water' molecule is activated and OH − nucleophile is generated, in turn determining the speed of the motor. We tested this hypothesis by identifying two hydrophobic amino acids, M195 and F259, in the catalytic space of gp17-ATPase that are in a position to modulate motor speed. Combinatorial mutagenesis demonstrated that hydrophobic substitutions were tolerated but polar or charged substitutions resulted in null or cold-sensitive/small-plaque phenotypes. Quantitative biochemical and single-molecule analyses showed that the mutant motors exhibited 1.8- to 2.5-fold lower rate of ATP hydrolysis, 2.5- to 4.5-fold lower DNA packaging velocity, and required an activator protein, gp16 for rapid firing of ATPases. These studies uncover a speed control mechanism that might allow selection of motors with optimal performance for organisms' survival.